Optical, X-Ray Diffraction, and Magnetic Properties of the Cobalt-Substituted Nickel Chromium Ferrites (CrCo𝑥Ni1−𝑥FeO4, 𝑥=0,0.2,0.4,0.6,0.8,1.0) Synthesized Using Sol-Gel Autocombustion Method - Sonal Singhal; Santosh Bhukal; Jagdish Singh; Kailash Chandra; S. Bansal (Journal of Nanotechnology)
Cobalt-substituted nickel chromium ferrites (CrCo𝑥Ni1−𝑥FeO4, 𝑥=0,0.2,0.4,0.6,0.8,1.0) have been synthesized using sol-gel autocombustion method and annealed at 400 °C, 600 °C, 800 °C, and 1000 °C. All the ferrite samples have been characterized using UV-VIS spectrophotometery, FT-IR spectroscopy, Transmission Electron Microscopy, powder X-Ray Diffraction, and magnetic measurements. Typical FT-IR spectra of the samples annealed at 400°C, 600°C, 800°C, and 1000°C exhibit two frequency bands in the range of ~480 cm−1 and ~590 cm−1 corresponding to the formation of octahedral and tetrahedral clusters of metal oxide, respectively. TEM images reveal that crystallite size increases from ~10 nm to ~45 nm as the annealing temperature is increased from 400°C to 1000°C. The unit cell parameter “a” is found to increase on increasing the cobalt concentration due to larger ionic radius of cobalt. Also, as the cobalt concentration increases, the saturation magnetization increases from 4.32 to 19.85 emu/g. This is due to the fact that cobalt ion replaces the less magnetic nickel ions. However, the coercivity decreases with increase in cobalt concentration due to the decrease in anisotropy field. The band gap has been calculated using UV-VIS spectrophotometry and has been found to decrease with the increase of particle size.